Honeycomb ceramic carrier, preparation method thereof and tail gas catalysis core body
By using a specific proportion of 4H-SiC and 6H-SiC, elemental silicon and silica in honeycomb ceramic carriers, the powder particle size and crystal ratio are optimized, and the problem of high cost of honeycomb ceramic carriers is solved, achieving high cost performance and good quality thermal diffusion properties.
Patent Information
- Application Number
- CN202411336466.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-24
AI Technical Summary
Existing honeycomb ceramic carriers are costly and have poor cost performance when efficiently trapping diesel engine emission particles. In particular, the high cost of high-purity SiC materials limits their application.
Using a specific ratio of 4H-SiC and 6H-SiC as the crystal phase of silicon carbide, combined with elemental silicon and silica, honeycombs with good porosity, pore capacity and thermal diffusion performance are prepared by optimizing the powder particle size and crystal ratio. Ceramic carrier, reducing production costs.
It realizes a low-cost but excellent performance honeycomb ceramic carrier, with better porosity, pore capacity and thermal diffusion coefficient, and higher cost-effectiveness, suitable for high-temperature applications.
Smart Images

Figure CN119285369A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of honeycomb ceramic carriers, specifically to a honeycomb ceramic carrier and its preparation method, and an exhaust gas catalyst core. Background Technology
[0002] In current technologies, honeycomb ceramic filters for efficiently capturing diesel engine particulate matter often use high-purity silicon carbide as the main aggregate. Among these, 4H-SiC, 6H-SiC, 3C-SiC, and 15R-SiC are different crystal forms of silicon carbide, each possessing unique physical and chemical properties that determine their applicability and advantages in applications such as honeycomb ceramics. The following is a comparison of these crystal forms in honeycomb ceramics: 3C-SiC has a cubic lattice structure, unlike other hexagonal SiC crystal forms, and its thermal conductivity is relatively low, potentially making it unsuitable for applications requiring extremely high thermal conductivity. 15R-SiC, compared to other crystal forms, has received less research and has fewer applications, requiring further investigation. 4H-SiC and 6H-SiC, due to their high thermal conductivity and good high-temperature stability, are very suitable for use in high-temperature honeycomb ceramics. In general, 4H-SiC and 6H-SiC are more commonly used in high-temperature applications such as honeycomb ceramics due to their excellent physical properties. Due to limited research, the application potential of 15R-SiC in cell ceramics remains to be further explored. The choice of each crystal form will depend on specific application requirements and performance specifications. Currently, commercially available SiC cell ceramic materials all use high-purity SiC, with 6H-SiC accounting for over 90% of the mass fraction, resulting in higher costs.
[0003] Therefore, finding a more cost-effective cellular ceramic carrier has become an urgent problem to be solved in this field. Summary of the Invention
[0004] The purpose of this invention is to provide a honeycomb ceramic carrier and its preparation method, as well as a tail gas catalyst core, which has better cost performance while ensuring better porosity, pore volume and thermal diffusivity.
[0005] To achieve the above objectives, the present invention provides the following technical solution:
[0006] A cellular ceramic carrier contains silicon carbide, the silicon carbide having crystalline phases including 4H-SiC and 6H-SiC, wherein the mass of 4H-SiC accounts for 13% to 30% of the total mass of the cellular ceramic carrier, the mass of 6H-SiC accounts for 40% to 55% of the total mass of the cellular ceramic carrier, and the porosity of the cellular ceramic carrier is 45% to 70%, preferably 50% to 65%.
[0007] In some embodiments of the present invention, the mass ratio of 4H-SiC to 6H-SiC is 1:(2-4), preferably 1:(2-3).
[0008] In some embodiments of the present invention, the cellular ceramic carrier further contains elemental silicon, wherein the mass of the elemental silicon accounts for 10-25% of the total mass of the cellular ceramic carrier, preferably 15-25%.
[0009] And / or, the cellular ceramic carrier further contains silicon dioxide, wherein the mass of the silicon dioxide accounts for 5 to 25% of the total mass of the cellular ceramic carrier, preferably 8 to 18%.
[0010] In some embodiments of the present invention, the thermal diffusivity of the honeycomb ceramic carrier is 5–25 mm. 2 / s, preferably 16-20mm 2 / s.
[0011] In some embodiments of the present invention, the raw materials of the cellular ceramic carrier include main materials and auxiliary materials, wherein the main materials include two or three of the following: a first silicon carbide powder with a particle size of 30 to 50 μm, a second silicon carbide powder with a particle size of 15 to 30 μm, and a third silicon carbide powder with a particle size of less than 15 μm.
[0012] Preferably, the particle size of the first silicon carbide powder is 35-45 μm, the particle size of the second silicon carbide powder is 20-30 μm, and the particle size of the third silicon carbide powder is 4-12 μm.
[0013] In some embodiments of the present invention, the mass ratio of 4H-SiC to 6H-SiC in the first silicon carbide powder is (0.15-0.25):1, preferably (0.17-0.23):1;
[0014] And / or, the mass ratio of 4H-SiC to 6H-SiC in the second silicon carbide powder is (0.3-0.4):1, preferably (0.3-0.35):1;
[0015] And / or, the mass ratio of 4H-SiC to 6H-SiC in the third silicon carbide powder is (0.15-0.25):1, preferably (0.15-0.2):1.
[0016] In some embodiments of the present invention, the main material further includes elemental silicon powder, metal oxide, clay, and / or the auxiliary materials include binders and pore-forming agents;
[0017] Preferably, the silicon carbide powder accounts for 60-90% of the mass of the main material, more preferably 75-85%; the elemental silicon powder accounts for 15-25% of the mass of the main material, more preferably 15-20%; the metal oxide accounts for 0.1-2.5% of the mass of the main material, more preferably 0.5-2%; the clay accounts for 0.1-2% of the mass of the main material, more preferably 0.5-1.5%; the binder accounts for 4-10% of the mass of the main material, more preferably 5-8%; and the pore-forming agent accounts for 2-30% of the mass of the main material, more preferably 5-15%.
[0018] In some embodiments of the present invention, the mass of the first silicon carbide powder accounts for 0% to 50% of the mass of the main material, more preferably 4% to 40%, the mass of the second silicon carbide powder accounts for 25% to 75% of the mass of the main material, more preferably 30% to 70%, and the mass of the third silicon carbide powder accounts for 0% to 5% of the mass of the main material, more preferably 1% to 4%.
[0019] Alternatively, the mass ratio of the first, second, and third silicon carbide powders is (0-50):(30-75):(0-5), wherein the mass of the first and third silicon carbide powders is not simultaneously zero.
[0020] In some embodiments of the present invention, the pore-forming agent is selected from at least one of polyacrylic acid derivatives, polyacrylamide derivatives, polyvinyl alcohol, polymethyl methacrylate microspheres, starch, and expanded microspheres;
[0021] And / or, the pore-forming agent has a D10 ≥ 10 μm and a D90 ≤ 35 μm.
[0022] In some embodiments of the present invention, the particle size of the elemental silicon powder is D10>1μm and D90<15μm, the particle size of the metal oxide is D10>2.8μm and D90<8μm, and the particle size of the clay is D10>2μm and D90<17μm.
[0023] And / or, the adhesive is selected from at least one of polyvinyl alcohol, polyethylene glycol, carboxymethyl cellulose, methyl cellulose, and ethyl cellulose;
[0024] In some embodiments of the present invention, the metal oxide is at least one selected from calcium oxide, sodium oxide, magnesium oxide, aluminum oxide, barium oxide, iron oxide, and copper oxide.
[0025] In some embodiments of the present invention, the pore density of the cellular ceramic carrier is 200-400 cpsi, preferably 275-305 cpsi.
[0026] In some embodiments of the present invention, the median pore size D50 of the cellular ceramic carrier is 10–30 μm, preferably 10–18 μm.
[0027] In some embodiments of the present invention, the pore volume of the honeycomb ceramic carrier is 0.18 to 0.6 mL / g, preferably 0.2 to 0.3 mL / g.
[0028] To achieve the above objectives, the present invention also provides the following technical solutions:
[0029] A method for preparing the above-mentioned honeycomb ceramic carrier, the method comprising the following steps:
[0030] S1, providing raw materials, said raw materials including silicon carbide powder, elemental silicon powder, metal oxide, clay, binder and pore-forming agent;
[0031] S2, the raw materials in step S1 are mixed, kneaded, pounded, extruded, dried, cut and sintered to obtain ceramic unit bodies;
[0032] S3, the ceramic unit is sequentially spliced, ground, and grafted to obtain the honeycomb ceramic carrier.
[0033] In some embodiments of the present invention, the silicon carbide powder includes two or three of the following: a first silicon carbide powder with a particle size of 30 to 50 μm, a second silicon carbide powder with a particle size of 15 to 30 μm, and a third silicon carbide powder with a particle size of less than 15 μm.
[0034] Preferably, the particle size of the first silicon carbide powder is 35-45 μm, the particle size of the second silicon carbide powder is 20-30 μm, and the particle size of the third silicon carbide powder is 4-12 μm.
[0035] In some embodiments of the present invention, the mass ratio of 4H-SiC to 6H-SiC in the first silicon carbide powder is (0.15-0.25):1, preferably (0.17-0.23):1;
[0036] And / or, the mass ratio of 4H-SiC to 6H-SiC in the second silicon carbide powder is (0.3-0.4):1, preferably (0.3-0.35):1;
[0037] And / or, the mass ratio of 4H-SiC to 6H-SiC in the third silicon carbide powder is (0.15-0.25):1, preferably (0.15-0.2):1.
[0038] In some embodiments of the present invention, step S2 includes a hole-plugging step between sintering and drying.
[0039] In some embodiments of the present invention, in step S2, the mixing of raw materials is carried out by first dry mixing and then wet mixing.
[0040] And / or, in step S2, the drying is performed using microwave drying;
[0041] And / or, in step S2, the sintering is performed by first sintering in an oxygen-free environment and then sintering in an oxygen-containing environment.
[0042] To achieve the above objectives, the present invention also provides the following technical solutions:
[0043] An exhaust gas catalyst core, the exhaust gas catalyst core comprising:
[0044] The aforementioned honeycomb ceramic carrier or the honeycomb ceramic carrier prepared by the aforementioned method; and
[0045] The catalyst is applied to the inner wall surface of the pores of the honeycomb ceramic carrier.
[0046] Other applicable areas will become apparent from the description provided in this disclosure.
[0047] The descriptions and specific examples in the invention summary are intended to be illustrative only and are not intended to limit the scope of this disclosure.
[0048] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0049] This invention provides a silicon carbide honeycomb ceramic structure with a special crystal phase ratio, achieving low cost and excellent performance. Specifically, by using a honeycomb ceramic carrier made of 4HSiC-6HSiC material with a specific crystal phase ratio, better performance is obtained, especially a thermal diffusivity of 5-25 mm. 2 This allows the performance of the honeycomb ceramic carrier to reach the level of existing technologies, while achieving lower production costs due to the specific ratio of 4HSiC-6HSiC crystalline phases in silicon carbide. Especially under high porosity conditions, the honeycomb ceramic carrier provided by this invention exhibits superior pore volume and thermal diffusivity, while also offering higher cost-effectiveness. Attached Figure Description
[0050] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0051] Figure 1 A flowchart illustrating the preparation method of the honeycomb ceramic carrier provided in the first embodiment of the present invention;
[0052] Figure 2 XRD patterns of high-purity silicon carbide, silicon carbide primary powder, silicon carbide secondary powder, and silicon carbide tertiary powder raw materials provided for the second embodiment of the present invention;
[0053] Figure 3 The images show the XRD patterns of the finished carriers of Comparative Examples 1, 2, 1, 5, and 8 of this invention. Detailed Implementation
[0054] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. It should be understood that the specific embodiments described herein are only for illustration and explanation of the present invention and are not intended to limit the present invention.
[0055] Any specific numerical values disclosed herein (including the endpoints of numerical ranges) are not limited to their exact values, but should be understood to also include values close to the exact value, such as all possible values within ±5% of the exact value. Furthermore, with respect to the disclosed numerical ranges, one or more new numerical ranges can be obtained by arbitrarily combining the endpoint values of the range, the endpoint values with specific point values within the range, and the specific point values themselves; these new numerical ranges should also be considered as specifically disclosed herein.
[0056] The terminology used in this disclosure is for the purpose of describing particular exemplary embodiments only and is not intended to be limiting. Unless the context clearly indicates otherwise, the singular forms “a,” “an,” and “the” as used in this disclosure are intended to include the plural forms as well. The terms “comprising,” “including,” “containing,” and “having” are inclusive and thus describe the presence of said features, elements, compositions, steps, integers, operations, and / or components, but do not exclude the presence or inclusion of one or more other features, integers, steps, operations, elements, components, and / or sets thereof. Although the open-ended term “comprising” should be understood as a non-limiting term used to describe and claim the various embodiments described in this disclosure, in some aspects it may instead be understood as a more restrictive and limiting term, such as “consisting of” or “substantially consisting of.” Thus, for any given embodiment describing a composition, material, component, element, feature, integer, operation, and / or process step, this disclosure also particularly includes embodiments consisting of or substantially consisting of such compositions, materials, components, elements, features, integers, operations, and / or process steps. In the case of “consisting of…”, the alternative embodiments exclude any additional compositions, materials, components, elements, features, integers, operations and / or process steps. In the case of “essentially composed of…”, any additional compositions, materials, components, elements, features, integers, operations and / or process steps that substantially affect the essential and novel characteristics are excluded from such embodiments. However, any compositions, materials, components, elements, features, integers, operations and / or process steps that do not substantially affect the essential and novel characteristics may be included in the embodiments.
[0057] Any method steps, processes, and operations described in this disclosure should not be construed as necessarily requiring them to be performed in a particular order as discussed or shown, unless explicitly specified. It should also be understood that additional or alternative steps may be used unless otherwise stated.
[0058] In this application, except where expressly stated, any matters or issues not mentioned are directly applicable to those known in the art without any modification. Furthermore, any implementation described in this disclosure may be freely combined with one or more other implementations described in this disclosure, and the resulting technical solutions or concepts shall be considered part of the original disclosure or original record of this application, and should not be regarded as new content not disclosed or anticipated in this disclosure, unless those skilled in the art consider the combination to be clearly unreasonable.
[0059] Unless otherwise stated, the terms used herein have the same meaning as commonly understood by those skilled in the art, and if a term is defined herein and its definition differs from the common understanding in the art, the definition herein shall prevail.
[0060] Unless otherwise stated, when % is mentioned in this document, it means wt.%.
[0061] It is worth noting that the definitions or explanations of some parameters in this invention specification are as follows:
[0062] Pore volume, also known as pore volume, refers to the total volume of micropores per unit mass of porous solid. It is one of the important characteristic values of porous adsorbents or catalysts, and is usually expressed as the volume of adsorbent micropores per unit weight of adsorbent, with the unit being cm3 / g.
[0063] Thermal diffusivity, usually denoted by α, is a physical quantity describing the ability of a material to transmit temperature within it. Its unit is square meters per second (m² / s), and it can be calculated using the formula α = λ / ρc, where λ represents thermal conductivity (W / (m·K)), ρ is density (kg / m³), and c is specific heat capacity (J / (kg·K)).¹¹ The thermal diffusivity reflects the rate at which temperature changes propagate within a material when subjected to thermal stimulation; a larger α value indicates a greater ability to diffuse temperature within the material, meaning that temperature changes propagate more rapidly within the material.
[0064] It is worth noting that, in the cumulative pore volume of the partition wall determined by mercury intrusion porosimetry, the pore diameter that accounts for 10% of the total pore volume is designated as D10, the pore diameter that accounts for 50% of the total pore volume is designated as D50, i.e., the median pore diameter, and the pore diameter that accounts for 90% of the total pore volume is designated as D90.
[0065] In the context of this disclosure, pore density refers to the number of pores per square inch in the cross-section of a cellular ceramic carrier, measured in cpsi. Pores here include both open and closed pores.
[0066] First aspect
[0067] A cellular ceramic carrier contains silicon carbide, wherein the crystalline phases of the silicon carbide include 4H-SiC and 6H-SiC, wherein the mass of 4H-SiC accounts for 13% to 30% of the total mass of the cellular ceramic carrier, the mass of 6H-SiC accounts for 40% to 55% of the total mass of the cellular ceramic carrier, and the porosity of the cellular ceramic carrier is 45% to 70%, preferably 50% to 65%.
[0068] The honeycomb ceramic carrier provided by the present invention has a higher cost performance while ensuring good porosity, pore volume and thermal diffusivity.
[0069] In some embodiments of the present invention, the mass ratio of 4H-SiC to 6H-SiC is 1:(2-4), preferably 1:2.
[0070] In some embodiments of the present invention, the cellular ceramic carrier further contains elemental silicon, wherein the mass of the elemental silicon accounts for 10-25% of the total mass of the cellular ceramic carrier, preferably 15-25%.
[0071] In some embodiments of the present invention, the cellular ceramic carrier further contains silicon dioxide, wherein the mass of the silicon dioxide accounts for 5 to 25% of the total mass of the cellular ceramic carrier, preferably 8 to 18%.
[0072] In some embodiments of the present invention, the thermal diffusivity of the honeycomb ceramic carrier is 5–25 mm. 2 / s, preferably 16-20mm 2 / s.
[0073] In some embodiments of the present invention, the raw materials of the cellular ceramic carrier include main materials and auxiliary materials, wherein the main materials include two or three of the following: a first silicon carbide powder with a particle size of 30 to 50 μm, a second silicon carbide powder with a particle size of 15 to 30 μm, and a third silicon carbide powder with a particle size of less than 15 μm.
[0074] In some embodiments of the present invention, the particle size of the first silicon carbide powder is 35-45 μm, the particle size of the second silicon carbide powder is 20-30 μm, and the particle size of the third silicon carbide powder is 4-12 μm.
[0075] In some embodiments of the present invention, the mass ratio of 4H-SiC to 6H-SiC in the first silicon carbide powder is (0.15-0.25):1, preferably (0.17-0.23):1.
[0076] In some embodiments of the present invention, the mass ratio of 4H-SiC to 6H-SiC in the second silicon carbide powder is (0.3-0.4):1, preferably (0.3-0.35):1.
[0077] In some embodiments of the present invention, the mass ratio of 4H-SiC to 6H-SiC in the third silicon carbide powder is (0.15-0.25):1, preferably (0.15-0.2):1.
[0078] In some embodiments of the present invention, the main material further includes elemental silicon powder, metal oxides, and clay.
[0079] In some embodiments of the present invention, the excipients include binders and pore-forming agents.
[0080] In some embodiments of the present invention, the mass of the silicon carbide powder accounts for 60-90%, more preferably 75-85%, of the mass of the main material; the mass of the elemental silicon powder accounts for 15-25%, more preferably 15-20%, of the mass of the main material; the mass of the metal oxide accounts for 0.1-2.5%, more preferably 0.5-2%, of the mass of the main material; the mass of the clay accounts for 0.1-2%, more preferably 0.5-1.5%, of the mass of the main material; the mass of the binder accounts for 4-10%, more preferably 5-8%, of the mass of the main material; and the mass of the pore-forming agent accounts for 2-30%, more preferably 5-15%, of the mass of the main material. In the context of the present invention, the total mass of the main materials—namely, silicon carbide powder, elemental silicon powder, metal oxide, and clay—is always 100%, meaning the total mass of the main materials refers to the total mass of silicon carbide powder, elemental silicon powder, metal oxide, and clay.
[0081] In some embodiments of the present invention, the mass of the first silicon carbide powder accounts for 0% to 50% of the mass of the main material, more preferably 4% to 40%, the mass of the second silicon carbide powder accounts for 25% to 75% of the mass of the main material, more preferably 30% to 70%, and the mass of the third silicon carbide powder accounts for 0% to 5% of the mass of the main material, more preferably 1% to 4%.
[0082] Alternatively, the mass ratio of the first, second, and third silicon carbide powders is (0-50):(30-75):(0-5), wherein the mass of the first and third silicon carbide powders is not simultaneously zero.
[0083] In some embodiments of the present invention, the pore-forming agent is selected from at least one of polyacrylic acid derivatives, polyacrylamide derivatives, polyvinyl alcohol derivatives, polymethyl methacrylate microspheres, starch, and expanded microspheres.
[0084] In some embodiments of the present invention, the pore-forming agent has a D10 ≥ 10 μm and a D90 ≤ 35 μm.
[0085] In some embodiments of the present invention, the particle size of the elemental silicon powder is D10>1μm and D90<15μm.
[0086] In some embodiments of the present invention, the particle size of the metal oxide is D10 > 2.8 μm and D90 < 8 μm.
[0087] In some embodiments of the present invention, the clay has a particle size specification of D10 > 2 μm and D90 < 17 μm.
[0088] In some embodiments of the present invention, the adhesive is selected from at least one of polyvinyl alcohol, polyethylene glycol, carboxymethyl cellulose, methyl cellulose, and ethyl cellulose.
[0089] In some embodiments of the present invention, the metal oxide is at least one selected from calcium oxide, sodium oxide, magnesium oxide, aluminum oxide, barium oxide, iron oxide, and copper oxide.
[0090] In some embodiments of the present invention, the pore density of the cellular ceramic carrier is 200-400 cpsi, preferably 275-305 cpsi.
[0091] In some embodiments of the present invention, the pore size of the honeycomb ceramic carrier is 10-30 μm, preferably 10-18 μm.
[0092] In other embodiments of the present invention, the porosity of the cellular ceramic carrier is 30-70%, preferably 35-60%.
[0093] In some embodiments of the present invention, the pore volume of the honeycomb ceramic carrier is 0.18 to 0.6 mL / g, preferably 0.2 to 0.3 mL / g.
[0094] It is worth noting that the honeycomb ceramic carrier provided by the present invention can be used as a tail gas catalytic core, and can be used for the purification and catalytic treatment of tail gas or exhaust gas. More specifically, it can be used for the catalytic purification treatment of exhaust gas generated by incomplete combustion of diesel.
[0095] In some embodiments of the present invention, the honeycomb ceramic carrier has a plurality of compartments extending along its longitudinal direction. At one end of the honeycomb ceramic carrier in the longitudinal direction, a portion of the compartments are sealed and blocked, while at the other end, a portion of the compartments are sealed and blocked. A partition wall is provided between the two types of compartments to allow them to be adjacent, and the partition wall is provided with a plurality of vents for airflow exchange between the two compartments.
[0096] Second aspect
[0097] See Figure 1 A method for preparing the above-mentioned honeycomb ceramic carrier includes the following steps: S1, providing raw materials, the raw materials including silicon carbide powder, elemental silicon powder, metal oxide, clay, binder and pore-forming agent; S2, mixing, kneading, sizing, extruding, drying, cutting and sintering the raw materials in step S1 to obtain ceramic unit bodies; S3, sequentially splicing, grinding and skinning the ceramic unit bodies to obtain the honeycomb ceramic carrier.
[0098] In some embodiments of the present invention, the silicon carbide powder includes two or three of the following: a first silicon carbide powder with a particle size of 30 to 50 μm, a second silicon carbide powder with a particle size of 15 to 30 μm, and a third silicon carbide powder with a particle size of less than 15 μm.
[0099] In some embodiments of the present invention, the particle size of the first silicon carbide powder is 35-45 μm, the particle size of the second silicon carbide powder is 20-30 μm, and the particle size of the third silicon carbide powder is 4-12 μm.
[0100] In some embodiments of the present invention, the mass ratio of 4H-SiC to 6H-SiC in the first silicon carbide powder is (0.15-0.25):1, preferably (0.17-0.23):1.
[0101] In some embodiments of the present invention, the mass ratio of 4H-SiC to 6H-SiC in the second silicon carbide powder is (0.3-0.4):1, preferably (0.3-0.35):1.
[0102] In some embodiments of the present invention, the mass ratio of 4H-SiC to 6H-SiC in the third silicon carbide powder is (0.15-0.25):1, preferably (0.15-0.2):1.
[0103] In some embodiments of the present invention, step S2 includes a hole-plugging step between sintering and drying.
[0104] In some embodiments of the present invention, in step S2, the mixing of raw materials is carried out by first dry mixing and then wet mixing.
[0105] In some embodiments of the present invention, step S2 is performed by microwave drying.
[0106] In some embodiments of the present invention, in step S2, the sintering is performed by first sintering in an oxygen-free environment and then sintering in an oxygen-rich environment.
[0107] Third aspect
[0108] An exhaust gas catalyst core includes: the honeycomb ceramic carrier described above or the honeycomb ceramic carrier prepared by the above method; and a catalyst coated on the inner wall surface of the pores of the honeycomb ceramic carrier.
[0109] It is worth noting that the exhaust gas catalytic core provided by the present invention can be used for the purification and catalytic treatment of exhaust gas or waste gas, and more specifically, it can be used for the catalytic purification treatment of waste gas generated by incomplete combustion of diesel.
[0110] Example 1
[0111] In this embodiment, relative to the main material, the proportion of silicon carbide powder is 80 wt.%, of which the proportion of first silicon carbide powder is 47 wt.%, the mass ratio of 4H-SiC to 6H-SiC in the first silicon carbide powder is 0.2:1, the proportion of second silicon carbide powder is 33 wt.%, the mass ratio of 4H-SiC to 6H-SiC in the second silicon carbide powder is 0.3:1, the proportion of elemental silicon powder is 18 wt.%, the proportion of clay is 0.5 wt.%, the proportion of metal oxide powder is 1.5 wt.%, the proportion of binder is 6.8 wt.%, and the proportion of pore-forming agent is 2.2 wt.%; the binder is polyethylene glycol; the pore-forming agent is polyacrylic acid and starch, the mass ratio of polyacrylic acid and starch in the pore-forming agent is 1:1; and the metal oxide is calcium oxide.
[0112] All the above raw materials were added to a plow-type mixer for dry mixing for 15 minutes at a speed of 95 rpm. After dry mixing, water was added for wet mixing, with the water content relative to the main material being 45.2 wt.%, for 5 minutes at a speed of 95 rpm. After wet mixing, the resulting mixture was fed into a bi-shaft kneader for kneading for 60 minutes. After kneading, the mixture was slurry-kneaded and then fed into an extruder to obtain unit cells. The unit cells were then subjected to microwave drying, pore plugging, degreasing, oxygen-free sintering, and oxidation sintering in sequence. Finally, they were spliced, ground, and grafted to obtain a honeycomb ceramic carrier.
[0113] Example 2
[0114] In this embodiment, relative to the main material, the proportion of silicon carbide powder is 75 wt.%, of which the proportion of first silicon carbide powder is 43 wt.%, the mass ratio of 4H-SiC to 6H-SiC in the first silicon carbide powder is 0.18:1, the proportion of second silicon carbide powder is 32 wt.%, the mass ratio of 4H-SiC to 6H-SiC in the second silicon carbide powder is 0.3:1, the proportion of elemental silicon powder is 20.8 wt.%, the proportion of clay is 1.5 wt.%, the proportion of metal oxide powder is 2.2 wt.%, the proportion of binder is 6.8 wt.%, and the proportion of pore-forming agent is 2.2 wt.%; the binder is carboxymethyl cellulose; the pore-forming agent is polylactic acid and starch, the mass ratio of polylactic acid and starch in the pore-forming agent is 1:1; and the metal oxide is sodium oxide.
[0115] All the above raw materials were added to a plow-type mixer for dry mixing for 15 minutes at a speed of 95 rpm. After dry mixing, water was added for wet mixing, with the water content relative to the main material being 45.2 wt.%, for 5 minutes at a speed of 95 rpm. After wet mixing, the resulting mixture was fed into a bi-shaft kneader for kneading for 60 minutes. After kneading, the mixture was slurry-kneaded and then fed into an extruder to obtain unit cells. The unit cells were then subjected to microwave drying, pore plugging, degreasing, oxygen-free sintering, and oxidation sintering in sequence. Finally, they were spliced, ground, and grafted to obtain a honeycomb ceramic carrier.
[0116] Example 3
[0117] In this embodiment, the proportion of silicon carbide powder is 77 wt.%, of which the proportion of first silicon carbide powder is 38 wt.% and the mass ratio of 4H-SiC to 6H-SiC in the first silicon carbide powder is 0.17:1; the proportion of second silicon carbide powder is 39 wt.% and the mass ratio of 4H-SiC to 6H-SiC in the second silicon carbide powder is 0.31:1; the proportion of elemental silicon powder is 19.8 wt.%; the proportion of clay is 1.5 wt.%; the proportion of metal oxide powder is 1.7 wt.%; the proportion of binder is 6.8 wt.%; and the proportion of pore-forming agent is 7 wt.%. The binder is methylcellulose; the pore-forming agent is polyvinyl butyral and starch, and the mass ratio of polyvinyl butyral to starch in the pore-forming agent is 1:1; and the metal oxide is magnesium oxide.
[0118] All the above raw materials were added to a plow-type mixer for dry mixing for 15 minutes at a speed of 95 rpm. After dry mixing, water was added for wet mixing, with the water content relative to the main material being 45.2 wt.%, for 5 minutes at a speed of 95 rpm. After wet mixing, the resulting mixture was fed into a bi-shaft kneader for kneading for 60 minutes. After kneading, the mixture was slurry-kneaded and then fed into an extruder to obtain unit cells. The unit cells were then subjected to microwave drying, pore plugging, degreasing, oxygen-free sintering, and oxidation sintering in sequence. Finally, they were spliced, ground, and grafted to obtain a honeycomb ceramic carrier.
[0119] Example 4
[0120] In this embodiment, the proportion of silicon carbide powder relative to the main material is 80 wt.%, wherein the proportion of first silicon carbide powder is 35 wt.%, and the mass ratio of 4H-SiC to 6H-SiC in the first silicon carbide powder is 0.16:1; the proportion of second silicon carbide powder is 40 wt.%, and the mass ratio of 4H-SiC to 6H-SiC in the second silicon carbide powder is 0.33:1; and the proportion of third silicon carbide powder is 5 wt.%, and the mass ratio of 4H-SiC to 6H-SiC in the third silicon carbide powder is... The mass ratio of 4H-SiC to 6H-SiC is 0.18:1, the proportion of elemental silica powder is 18 wt.%, the proportion of clay is 0.5 wt.%, the proportion of metal oxide powder is 1.5 wt.%, the proportion of binder is 6.8 wt.%, and the proportion of pore-forming agent is 9.3 wt.%; the binder is ethyl cellulose; the pore-forming agent is polyacrylic acid, starch, and polyvinyl alcohol, and the mass ratio of polyacrylic acid, starch, and polyvinyl alcohol in the pore-forming agent is 1:1:1; the metal oxide is copper oxide.
[0121] All the above raw materials were added to a plow-type mixer for dry mixing for 15 minutes at a speed of 95 rpm. After dry mixing, water was added for wet mixing, with the water content relative to the main material being 45.5 wt.%, for 5 minutes at a speed of 95 rpm. After wet mixing, the resulting mixture was fed into a bi-shaft kneader for kneading for 60 minutes. After kneading, the mixture was kneaded into mud, and then fed into an extruder to extrude unit bodies. The unit bodies were then subjected to microwave drying, pore plugging, degreasing, oxygen-free sintering, and oxidation sintering in sequence. Finally, they were spliced, ground, and grafted to obtain a honeycomb ceramic carrier.
[0122] Example 5
[0123] In this embodiment, the proportion of silicon carbide powder relative to the main material is 83 wt.%, wherein the proportion of first silicon carbide powder is 35 wt.%, and the mass ratio of 4H-SiC to 6H-SiC in the first silicon carbide powder is 0.2:1; the proportion of second silicon carbide powder is 45 wt.%, and the mass ratio of 4H-SiC to 6H-SiC in the second silicon carbide powder is 0.36:1; the proportion of third silicon carbide powder is 5 wt.%, and the mass ratio of 4H-SiC to 6H-SiC in the third silicon carbide powder is 0.36:1; the proportion of third silicon carbide powder is 5 wt.%, and the mass ratio of 4H-SiC to 6H-SiC in the third silicon carbide powder is 0.2:1; the proportion of second silicon carbide powder is 45 wt.%, and the mass ratio of 4H-SiC to 6H-SiC in the third silicon carbide powder is 0.36:1; the proportion of third silicon carbide powder is 5 wt.%, and the mass ratio of 4H-SiC to 6H-SiC in the third silicon carbide powder is 0.2:1; the proportion of third silicon carbide powder is 43 wt.%, and the mass ratio of 4H-SiC to 6H-SiC in the third silicon carbide powder is 0.36 ... mass ratio of third silicon carbide powder is 4H-SiC to 6H-SiC in the third silicon carbide powder is 43 wt.%, and the mass ratio of third silicon carbide powder is 43 wt.%, and the mass ratio of third silicon carbide powder is 43 The mass ratio of SiC to 6H-SiC is 0.22:1, the proportion of elemental silicon powder is 15.2 wt.%, the proportion of clay is 0.5 wt.%, the proportion of metal oxide powder is 1.3 wt.%, the proportion of binder is 6.8 wt.%, and the proportion of pore-forming agent is 10.1 wt.%; the binder is polyethylene glycol; the pore-forming agent is polyvinyl acetate, starch, and polyvinyl alcohol, and the mass ratio of polyvinyl acetate, starch, and polyvinyl alcohol in the pore-forming agent is 1:1:1; the metal oxide is iron oxide.
[0124] All the above raw materials were added to a plow-type mixer for dry mixing for 15 minutes at a speed of 95 rpm. After dry mixing, water was added for wet mixing, with the water content relative to the main material being 46 wt.%, for 5 minutes at a speed of 95 rpm. After wet mixing, the resulting mixture was fed into a bi-shaft kneader for kneading for 60 minutes. After kneading, the mixture was kneaded into mud, and then fed into an extruder to extrude unit bodies. The unit bodies were then subjected to microwave drying, pore plugging, degreasing, oxygen-free sintering, and oxidation sintering in sequence. Finally, they were spliced, ground, and grafted to obtain a honeycomb ceramic carrier.
[0125] Example 6
[0126] In this embodiment, the proportion of silicon carbide powder relative to the main material is 80 wt.%, wherein the proportion of first silicon carbide powder is 25 wt.%, and the mass ratio of 4H-SiC to 6H-SiC in the first silicon carbide powder is 0.25:1; the proportion of second silicon carbide powder is 50 wt.%, and the mass ratio of 4H-SiC to 6H-SiC in the second silicon carbide powder is 0.32:1; and the proportion of third silicon carbide powder is 5 wt.%, and the mass ratio of 4H-SiC to 6H-SiC in the third silicon carbide powder is 0.32:1. The mass ratio of SiC to 6H-SiC is 0.19:1, the proportion of elemental silica powder is 18.2 wt.%, the proportion of clay is 0.5 wt.%, the proportion of metal oxide powder is 1.3 wt.%, the proportion of binder is 6.8 wt.%, and the proportion of pore-forming agent is 13.5 wt.%; the binder is polyethylene glycol; the pore-forming agent is polyvinyl alcohol and polymethyl methacrylate microspheres, and the mass ratio of polyvinyl alcohol and polymethyl methacrylate microspheres in the pore-forming agent is 1:1; the metal oxide is alumina.
[0127] All the above raw materials were added to a plow-type mixer for dry mixing for 15 minutes at a speed of 95 rpm. After dry mixing, water was added for wet mixing, with the water content relative to the main material being 46 wt.%, for 5 minutes at a speed of 95 rpm. After wet mixing, the resulting mixture was fed into a bi-shaft kneader for kneading for 60 minutes. After kneading, the mixture was kneaded into mud, and then fed into an extruder to extrude unit bodies. The unit bodies were then subjected to microwave drying, pore plugging, degreasing, oxygen-free sintering, and oxidation sintering in sequence. Finally, they were spliced, ground, and grafted to obtain a honeycomb ceramic carrier.
[0128] Example 7
[0129] In this embodiment, the proportion of silicon carbide powder relative to the main material is 80 wt.%, wherein the proportion of first silicon carbide powder is 15 wt.%, and the mass ratio of 4H-SiC to 6H-SiC in the first silicon carbide powder is 0.23:1; the proportion of second silicon carbide powder is 60 wt.%, and the mass ratio of 4H-SiC to 6H-SiC in the second silicon carbide powder is 0.38:1; and the proportion of third silicon carbide powder is 5 wt.%, and the mass ratio of 4H-SiC to 6H-SiC in the third silicon carbide powder is 0.38:1. The mass ratio of -SiC to 6H-SiC is 0.13:1, the proportion of elemental silica powder is 18 wt.%, the proportion of clay is 0.5 wt.%, the proportion of metal oxide powder is 1.5 wt.%, the proportion of binder is 6.8 wt.%, and the proportion of pore-forming agent is 17.6 wt.%; the binder is ethyl cellulose; the pore-forming agent is polyvinyl alcohol and polymethyl methacrylate microspheres, and the mass ratio of polyvinyl alcohol and polymethyl methacrylate microspheres in the pore-forming agent is 1:1; the metal oxide is calcium oxide.
[0130] All the above raw materials were added to a plow-type mixer for dry mixing for 15 minutes at a speed of 95 rpm. After dry mixing, water was added for wet mixing, with the water content relative to the main material being 46.5 wt.%, for 5 minutes at a speed of 95 rpm. After wet mixing, the resulting mixture was fed into a bi-shaft kneader for kneading for 60 minutes. After kneading, the mixture was kneaded into mud, and then fed into an extruder to extrude unit bodies. The unit bodies were then subjected to microwave drying, pore plugging, degreasing, oxygen-free sintering, and oxidation sintering in sequence. Finally, they were spliced, ground, and grafted to obtain a honeycomb ceramic carrier.
[0131] Example 8
[0132] In this embodiment, the proportion of silicon carbide powder relative to the main material is 80 wt.%, wherein the proportion of first silicon carbide powder is 5 wt.%, and the mass ratio of 4H-SiC to 6H-SiC in the first silicon carbide powder is 0.25:1; the proportion of second silicon carbide powder is 70 wt.%, and the mass ratio of 4H-SiC to 6H-SiC in the second silicon carbide powder is 0.3:1; and the proportion of third silicon carbide powder is 5 wt.%, and the mass ratio of 4H-SiC to 6H-SiC in the third silicon carbide powder is 0.3:1. The mass ratio of 4H-SiC to 6H-SiC is 0.25:1. The proportion of elemental silica powder is 18 wt.%, clay is 0.5 wt.%, metal oxide powder is 1.5 wt.%, binder is 2 wt.%, and pore-forming agent is 22.7 wt.%. The binder is ethyl cellulose. The pore-forming agent is polyacrylic acid, polyacrylamide, and starch, with a mass ratio of polyacrylic acid, polyacrylamide, and starch of 1:1. The metal oxide is barium oxide.
[0133] All the above raw materials were added to a plow-type mixer for dry mixing for 15 minutes at a speed of 95 rpm. After dry mixing, water was added for wet mixing, with the water content relative to the main material being 46.8 wt.%, for 5 minutes at a speed of 95 rpm. After wet mixing, the resulting mixture was fed into a bi-shaft kneader for kneading for 60 minutes. After kneading, the mixture was kneaded into mud, and then fed into an extruder to extrude unit bodies. The unit bodies were then subjected to microwave drying, pore plugging, degreasing, oxygen-free sintering, and oxidation sintering in sequence. Finally, they were spliced, ground, and grafted to obtain a honeycomb ceramic carrier.
[0134] Example 9
[0135] In this embodiment, relative to the main material, the proportion of silicon carbide powder is 80 wt.%, excluding the first silicon carbide powder; the proportion of the second silicon carbide powder is 75 wt.%, with a 4H-SiC to 6H-SiC mass ratio of 0.4:1 in the second silicon carbide powder; the proportion of the third silicon carbide powder is 5 wt.%, with a 4H-SiC to 6H-SiC mass ratio of 0.15:1 in the third silicon carbide powder; the proportion of elemental silicon powder is 17.8 wt.%; the proportion of clay is 0.5 wt.%; the proportion of metal oxide powder is 1.7 wt.%; the proportion of binder is 2 wt.%; and the proportion of pore-forming agent is 23.23 wt.%. The binder is methylcellulose; the pore-forming agent is polyacrylic acid, starch, and polyacrylamide, with a pore-forming agent mass ratio of polyacrylic acid, starch, and polyacrylamide of 1:1:1; and the metal oxide is sodium oxide.
[0136] All the above raw materials were added to a plow-type mixer for dry mixing for 15 minutes at a speed of 95 rpm. After dry mixing, water was added for wet mixing, with the water content relative to the main material being 46.8 wt.%, for 5 minutes at a speed of 95 rpm. After wet mixing, the resulting mixture was fed into a bi-shaft kneader for kneading for 60 minutes. After kneading, the mixture was kneaded into mud, and then fed into an extruder to extrude unit bodies. The unit bodies were then subjected to microwave drying, pore plugging, degreasing, oxygen-free sintering, and oxidation sintering in sequence. Finally, they were spliced, ground, and grafted to obtain a honeycomb ceramic carrier.
[0137] Comparative Example 1
[0138] In this embodiment, relative to the main material, the proportion of silicon carbide powder is 80 wt.%, using high-purity silicon carbide powder with a single particle size of 30.3 μm. The mass ratio of 4H-SiC to 6H-SiC in the high-purity silicon carbide powder is 0.05:1. The proportion of elemental silicon powder is 18 wt.%, the proportion of clay is 0.5 wt.%, the proportion of metal oxide powder is 1.5 wt.%, the proportion of binder is 6.8 wt.%, and the proportion of pore-forming agent is 3 wt.%. The binder is ethyl cellulose; the pore-forming agent is polyacrylic acid and starch, with a mass ratio of polyacrylic acid and starch of 1:1; and the metal oxide is alumina.
[0139] All the above raw materials were added to a plow-type mixer for dry mixing for 15 minutes at a speed of 95 rpm. After dry mixing, water was added for wet mixing, with the water content relative to the main material being 45.2 wt.%, for 5 minutes at a speed of 95 rpm. After wet mixing, the resulting mixture was fed into a bi-shaft kneader for kneading for 60 minutes. After kneading, the mixture was slurry-kneaded and then fed into an extruder to obtain unit cells. The unit cells were then subjected to microwave drying, pore plugging, degreasing, oxygen-free sintering, and oxidation sintering in sequence. Finally, they were spliced, ground, and grafted to obtain a honeycomb ceramic carrier.
[0140] Comparative Example 2
[0141] In this embodiment, relative to the main material, the proportion of silicon carbide powder is 80 wt.%, using high-purity silicon carbide powder with a single particle size of 30.1 μm. The mass ratio of 4H-SiC to 6H-SiC in the high-purity silicon carbide powder is 0.03:1. The proportion of elemental silicon powder is 18 wt.%, the proportion of clay is 0.5 wt.%, the proportion of metal oxide powder is 1.5 wt.%, the proportion of binder is 6.8 wt.%, and the proportion of pore-forming agent is 2.8 wt.%. The binder is carboxymethyl cellulose; the pore-forming agent is polyacrylic acid and starch, with a mass ratio of polyacrylic acid and starch of 1:1; and the metal oxide is magnesium oxide.
[0142] All the above raw materials were added to a plow-type mixer for dry mixing for 15 minutes at a speed of 95 rpm. After dry mixing, water was added for wet mixing, with the water content relative to the main material being 45.2 wt.%, for 5 minutes at a speed of 95 rpm. After wet mixing, the resulting mixture was fed into a bi-shaft kneader for kneading for 60 minutes. After kneading, the mixture was slurry-kneaded and then fed into an extruder to obtain unit cells. The unit cells were then subjected to microwave drying, pore plugging, degreasing, oxygen-free sintering, and oxidation sintering in sequence. Finally, they were spliced, ground, and grafted to obtain a honeycomb ceramic carrier.
[0143] Comparative Example 3
[0144] In this embodiment, relative to the main material, the proportion of silicon carbide powder is 80 wt.%, using high-purity silicon carbide powder with a single particle size of 30.5 μm. The mass ratio of 4H-SiC to 6H-SiC in the high-purity silicon carbide powder is 0.05:1. The proportion of elemental silicon powder is 18 wt.%, the proportion of clay is 0.5 wt.%, the proportion of metal oxide powder is 1.5 wt.%, the proportion of binder is 6.8 wt.%, and the proportion of pore-forming agent is 23 wt.%. The binder is glycerol; the pore-forming agent is polyacrylic acid, polyacrylamide, and starch, with a mass ratio of polyacrylic acid, polyacrylamide, and starch of 1:1; the metal oxide is barium oxide.
[0145] All the above raw materials were added to a plow-type mixer for dry mixing for 15 minutes at a speed of 95 rpm. After dry mixing, water was added for wet mixing, with the water content relative to the main material being 45.2 wt.%, for 5 minutes at a speed of 95 rpm. After wet mixing, the resulting mixture was fed into a bi-shaft kneader for kneading for 60 minutes. After kneading, the mixture was slurry-kneaded and then fed into an extruder to obtain unit cells. The unit cells were then subjected to microwave drying, pore plugging, degreasing, oxygen-free sintering, and oxidation sintering in sequence. Finally, they were spliced, ground, and grafted to obtain a honeycomb ceramic carrier.
[0146] Compared to Example 1, Comparative Examples 1 and 2 used high-purity silicon carbide powder with a single particle size, and the mass ratio of 4H-SiC to 6H-SiC in the powder was less than 0.1:1. Compared to Example 9, Comparative Example 3 used high-purity silicon carbide powder with a single particle size, and the mass ratio of 4H-SiC to 6H-SiC in the powder was less than 0.1:1.
[0147] The particle size distribution of silicon carbide powder in the above embodiments and comparative examples is shown in Table 1 below.
[0148] Table 1. Partial formulations of each embodiment and comparative example.
[0149]
[0150]
[0151] Table 2 below shows the product performance of each embodiment and comparative example. The crystal phases were analyzed using an XRD (X-ray diffractometer), model JS / YQXRD-201, with a scanning angle range of 10°–80°, a scanning speed of 0.2 s / step, and a scanning step of 0.02° / step. The median pore size, average pore size, porosity, and pore volume were measured using mercury porosimetry. Samples with dimensions of 10 mm * 10 mm * 15 mm were prepared and measured using a MicroActiveAutoPore V9600 VerSion 2.03.00 instrument from MicroPort Systems, Inc. The testing method conforms to the national standard GB / T21650.1-2008. The thermal diffusivity test method was a laser thermal conductivity meter. A sample with a side length of 10mm*10mm and a thickness of 1mm was cut and measured using a German Netzsch laser thermal conductivity meter (LFA467) at a heating interval of 50k / min. The test method was in accordance with the national standard GB / T22588-2008.
[0152] Table 2. Performance of the honeycomb ceramic carrier in each embodiment and comparative example.
[0153]
[0154] It is worth noting that during the preparation process, 6H-SiC will be transformed into SiO2 and CO2. At this time, the content of 6H-SiC crystal phase will decrease, while the content of SiO2 will increase, resulting in an increase in the ratio of 4H-SiC to 6H-SiC.
[0155] Compared with Examples 1 to 9, the SiC powder with a special crystal phase ratio and lower cost is used to prepare the product. Among them, Example 1 has similar thermal diffusivity, porosity, and pore volume to Comparative Examples 1 and 2. Compared with Comparative Example 3, Examples 8 and 9 have higher thermal diffusivity under high porosity conditions. This shows that the SiC powder with a special crystal phase ratio and lower cost used in this invention is beneficial to prepare a honeycomb ceramic carrier with properties similar to high-purity SiC honeycomb ceramics without reducing product performance. It also has a special crystal phase ratio, in which the 4H and 6H crystal phase ratio is 0.25 to 0.5. In the case of high porosity, the honeycomb ceramic carrier of this invention has higher thermal conductivity.
[0156] See Figure 2 , Figure 2The XRD patterns of the following raw materials are shown from top to bottom: high-purity silicon carbide (1), silicon carbide primary powder (2), silicon carbide secondary powder (3), and silicon carbide tertiary powder (4). The figures show that all four SiC raw materials are composed of 4H-SiC and 6H-SiC crystal phases, with six main peaks representing the 6H-SiC crystal phase. The two main peaks represent the 4H-SiC crystal phase. 4H-SiC is a hexagonal silicon carbide with a stacking sequence of 4 repeating units along the c-axis, and its basic stacking sequence is ABAC...; 6H-SiC is a hexagonal silicon carbide with a stacking sequence of 6 repeating units along the c-axis, and its basic stacking sequence is ABCACB...; Each crystal phase was analyzed by X-ray diffraction (XRD) using a JS / YQXRD-201 instrument with a scanning angle range of 10° to 80°, a scanning speed of 0.2 s / step, and a scanning step of 0.02° / step; the semi-quantitative XRD method is GB_T42676-2023.
[0157] It can be seen that the mass ratio of 4H-SiC to 6H-SiC in the high-purity silicon carbide powder raw material is 0.05, the mass ratio of 6H-SiC exceeds 90%, and the peak value of 4H-SiC is significantly lower than that of the other three raw materials. Elemental silicon powder (which accounts for a small proportion and is not included in the analysis) is also present. Figure 2 The proportion of elemental silicon powder is 0.5% (as indicated in the text). The mass ratio of 4H-SiC to 6H-SiC in the primary silicon carbide powder is 0.19, of which elemental silicon powder accounts for 0.1%. The mass ratio of 4H-SiC to 6H-SiC in the secondary silicon carbide powder is 0.36, of which elemental silicon powder accounts for 0.2%. The mass ratio of 4H-SiC to 6H-SiC in the tertiary silicon carbide powder is 0.19, of which elemental silicon powder accounts for 0.58%.
[0158] See Figure 3 , Figure 3 The images are XRD patterns of the finished carriers from top to bottom: Comparative Example 1 (5), Comparative Example 2 (6), Example 1 (7), Example 5 (8), and Example 8 (9). From the XRD patterns of each product, it can be seen that the finished products obtained from the above examples and comparative examples, i.e., the honeycomb ceramic carriers, contain a total of four crystalline phases: 4H-SiC(◆) and The peak value of 4H-SiC in the comparative examples is significantly lower. Specifically, the mass ratio of 4H-SiC to 6H-SiC in Comparative Example 1 (10) is 0.072, the mass ratio of 4H-SiC to 6H-SiC in Comparative Example 2 (11) is 0.067, the mass ratio of 4H-SiC to 6H-SiC in Example 1 (12) is 0.412, the mass ratio of 4H-SiC to 6H-SiC in Example 5 (13) is 0.279, and the mass ratio of 4H-SiC to 6H-SiC in Example 8 (14) is 0.395. It can be seen that the peak value of the 4H-SiC in the comparative examples is significantly lower or even tends to be stable, while the peak value of 6H-SiC is higher. In contrast, the peak value of the 4H-SiC in the examples is higher, while the peak value of 6H-SiC is lower than that of the comparative examples.
[0159] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims. Furthermore, specific examples have been used in the specification to illustrate the principles and implementation methods of the present invention. The above description of the embodiments is only for the purpose of helping to understand the method and core ideas of the present invention, and the content of this specification should not be construed as a limitation of the present invention.
Claims
1. A honeycomb ceramic carrier, characterized in that: The honeycomb ceramic carrier contains silicon carbide, and the crystal phase of the silicon carbide includes 4H-SiC and 6H-SiC. The mass of the 4H-SiC accounts for 13% to 30% of the total mass of the honeycomb ceramic carrier, and the mass of the 6H-SiC accounts for 40% to 55% of the total mass of the honeycomb ceramic carrier. The porosity of the honeycomb ceramic carrier is 45% to 70%, preferably 50 to 65%.
2. The honeycomb ceramic carrier according to claim 1, characterized in that: The mass ratio of the 4H-SiC to the 6H-SiC is 1:(2-4), preferably 1:
2.
3. The honeycomb ceramic carrier according to claim 1, characterized in that: The honeycomb ceramic carrier further contains elemental silicon, the mass of which accounts for 10-25% of the total mass of the honeycomb ceramic carrier, preferably 15-25%; And / or, the honeycomb ceramic carrier further contains silicon dioxide, and the mass of the silicon dioxide accounts for 5-25%, preferably 8-18% of the total mass of the honeycomb ceramic carrier.
4. The honeycomb ceramic carrier according to claim 1, characterized in that: The thermal diffusion coefficient of the honeycomb ceramic carrier is 5 to 25 mm 2 / s, preferably 16 to 20 mm 2 / s.
5. The honeycomb ceramic carrier according to claim 1, characterized in that: The raw materials of the honeycomb ceramic carrier include main materials and auxiliary materials, wherein the main materials include two or three of the following: a first silicon carbide powder with a particle size of 30 to 50 μm, a second silicon carbide powder with a particle size of 15 to 30 μm, and a third silicon carbide powder with a particle size less than 15 μm; Preferably, the particle size of the first silicon carbide powder is 35 to 45 μm, the particle size of the second silicon carbide powder is 20 to 30 μm, and the particle size of the third silicon carbide powder is 4 to 12 μm.
6. The honeycomb ceramic carrier according to claim 5, characterized in that: The mass ratio of 4H-SiC to 6H-SiC in the first silicon carbide powder is (0.15-0.25):1, preferably (0.17-0.23):1; And / or, the mass ratio of 4H-SiC to 6H-SiC in the second silicon carbide powder is (0.3-0.4):1, preferably (0.3-0.35):1; And / or, the mass ratio of 4H-SiC to 6H-SiC in the third silicon carbide powder is (0.15-0.25):1, preferably (0.15-0.2):
1.
7. The honeycomb ceramic carrier according to claim 5 or 6, characterized in that: The main material further comprises elemental silicon powder, metal oxide, clay, and / or the auxiliary material comprises a binder and a pore former; Preferably, the mass of the silicon carbide powder accounts for 60-90% of the mass of the main material, more preferably 75-85%, the mass of the elemental silicon powder accounts for 15-25% of the mass of the main material, more preferably 15-20%, the mass of the metal oxide accounts for 0.1-2.5% of the mass of the main material, more preferably 0.5-2%, the mass of the clay accounts for 0.1-2% of the mass of the main material, more preferably 0.5-1.5%, the mass of the binder accounts for 4-10% of the mass of the main material, more preferably 5-8%, and the mass of the pore-forming agent accounts for 2-30% of the mass of the main material, more preferably 5-15%.
8. The honeycomb ceramic carrier according to claim 7, characterized in that: The pore-forming agent is selected from at least one of polyacrylic acid, polyacrylamide, polyvinyl alcohol, polymethyl methacrylate microspheres, starch, and expanded microspheres; And / or, the pore former has a D10 ≥ 10 μm and a D90 ≤ 35 μm.
9. The honeycomb ceramic carrier according to claim 7, characterized in that: The particle size specifications of the elemental silicon powder are D10>1μm and D90<15μm, the particle size specifications of the metal oxide are D10>2.8μm and D90<8μm, and the particle size specifications of the clay are D10>2μm and D90<17μm; And / or, the binder is selected from at least one of polyvinyl alcohol, polyethylene glycol, carboxymethyl cellulose, methyl cellulose, and ethyl cellulose; And / or, the metal oxide is at least one selected from calcium oxide, sodium oxide, magnesium oxide, aluminum oxide, barium oxide, iron oxide, and copper oxide.
10. The honeycomb ceramic carrier according to claim 7, characterized in that: The mass of the first silicon carbide powder accounts for 0% to 50% of the mass of the main material, more preferably 4 to 40%, the mass of the second silicon carbide powder accounts for 30% to 75% of the mass of the main material, more preferably 30 to 40%, the mass of the third silicon carbide powder accounts for 0 to 5% of the mass of the main material, more preferably 1 to 4%; Alternatively, the mass ratio of the first, second and third silicon carbide powders is (0-50):(30-75):(0-5), wherein the masses of the first and third silicon carbide powders are not zero at the same time.
11. The honeycomb ceramic carrier according to any one of claims 1 to 6, characterized in that: The pore density of the honeycomb ceramic carrier is 200-400 cpsi, preferably 275-305 cpsi.
12. The honeycomb ceramic carrier according to any one of claims 1 to 6, characterized in that: The median pore diameter D50 of the honeycomb ceramic carrier is 10 to 30 μm, preferably 10 to 18 μm.
13. The honeycomb ceramic carrier according to any one of claims 1 to 6, characterized in that: The pore volume of the honeycomb ceramic carrier is 0.18 to 0.6 mL / g, preferably 0.2 to 0.3 mL / g.
14. A method for preparing the honeycomb ceramic carrier according to any one of claims 1 to 13, characterized in that: The method comprises the following steps: S1, providing raw materials, wherein the raw materials include silicon carbide powder, elemental silicon powder, metal oxide, clay, a binder and a pore former; S2, mixing, kneading, mixing, extruding, drying, cutting and sintering the raw materials in step S1 to obtain a ceramic unit body; S3, the ceramic unit bodies are sequentially subjected to splicing, skin grinding and skin grafting processes to obtain the honeycomb ceramic carrier.
15. The method according to claim 14, characterized in that The silicon carbide powder comprises two or three of the following: a first silicon carbide powder having a particle size of 30 to 50 μm, a second silicon carbide powder having a particle size of 15 to 30 μm, and a third silicon carbide powder having a particle size of less than 15 μm; Preferably, the particle size of the first silicon carbide powder is 35 to 45 μm, the particle size of the second silicon carbide powder is 20 to 30 μm, and the particle size of the third silicon carbide powder is 4 to 12 μm.
16. The method according to claim 14, characterized in that The mass ratio of 4H-SiC to 6H-SiC in the first silicon carbide powder is (0.15-0.25):1, preferably (0.17-0.23):1; And / or, the mass ratio of 4H-SiC to 6H-SiC in the second silicon carbide powder is (0.3-0.4):1, preferably (0.3-0.35):1; And / or, the mass ratio of 4H-SiC to 6H-SiC in the third silicon carbide powder is (0.15-0.25):1, preferably (0.15-0.2):
1.
17. The method according to any one of claims 14 to 16, characterized in that: In the step S2, there is also a pore plugging step between sintering and drying.
18. The method according to any one of claims 14 to 16, characterized in that: In step S2, the raw materials are mixed by first dry mixing and then wet mixing; And / or, in step S2, the drying is performed by microwave drying; And / or, in the step S2, the sintering is performed by first sintering without oxygen and then sintering with oxygen.
19. An exhaust gas catalytic core, characterized in that: The exhaust gas catalytic core comprises: The honeycomb ceramic carrier according to any one of claims 1 to 13 or the honeycomb ceramic carrier prepared by the method according to any one of claims 14 to 18; and The catalyst is coated on the inner wall surface of the pores of the honeycomb ceramic carrier.
Citation Information
Patent Citations
Silicon carbide ceramic and honeycomb structure
CN103140455A
Electric-conduction honeycomb silicon carbide and preparation method thereof
CN110407602A
Silicon carbide porous ceramic and preparation method thereof
CN118344153A
Manufacturing method for ceramic porous body, and ceramic porous body
JP2005239471A
Method for producing silicon carbide ceramic and method for producing honeycomb structure
US20130207322A1